The progress of microenvironment-targeted therapies in brain metastases - Long, Lifu; Yi, Zhenjie; Zeng, Yu; Liu, Zhixiong (Frontiers in Molecular Biosciences, 2023)
The incidence of brain metastases (BrM) has become a growing concern recently. It is a common and often fatal manifestation in the brain during the end-stage of many extracranial primary tumors. Increasing BrM diagnoses can be attributed to improvements in primary tumor treatments, which have extended patients’ lifetime, and allowed for earlier and more efficient detection of brain lesions. Currently, therapies for BrM encompass systemic chemotherapy, targeted therapy, and immunotherapy. Systemic chemotherapy regimens are controversial due to their associated side effects and limited efficacy. Targeted and immunotherapies have garnered significant attention in the medical field: they target specific molecular sites and modulate specific cellular components. However, multiple difficulties such as drug resistance and low permeability of the blood-brain barrier (BBB) remain significant challenges. Thus, there is an urgent need for novel therapies. Brain microenvironments consist of cellular components including immune cells, neurons, endothelial cells as well as molecular components like metal ions, nutrient molecules. Recent research indicates that malignant tumor cells can manipulate the brain microenvironment to change the anti-tumoral to a pro-tumoral microenvironment, both before, during, and after BrM. This review compares the characteristics of the brain microenvironment in BrM with those in other sites or primary tumors. Furthermore, it evaluates the preclinical and clinical studies of microenvironment-targeted therapies for BrM. These therapies, due to their diversity, are expected to overcome drug resistance or low permeability of the BBB with low side effects and high specificity. This will ultimately lead to improved outcomes for patients with secondary brain tumors.